2020
DOI: 10.21203/rs.2.17004/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Under-nutrition among Children under Five Years of Age in Ethiopia

Abstract: Background: Ethiopia is one of the developing countries where child under-nutrition is prevalent. Prior studies employed three anthropometric indicators for identifying factors of children’s under-nutrition. This study aimed at identifying factors of child under-nutrition using a single composite index of anthropometric indicator. Methods: Data from Ethiopia’s Demographic and Health Survey 2016 was the base for studying under-nutrition in a sample of 9494 children below 59 months. A single composite index of u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(55 reference statements)
2
2
0
Order By: Relevance
“…Knowledge itself is influenced by many factors, one of which is the level of education and age [26]. This research is in line with the research conducted by Aridiyah and Rohmawati [27] and Kassie and Workie [28]. The studies stated that one of the factors that influence the occurrence of stunting in children is the mother's education and knowledge.…”
Section: Discussionsupporting
confidence: 86%
“…Knowledge itself is influenced by many factors, one of which is the level of education and age [26]. This research is in line with the research conducted by Aridiyah and Rohmawati [27] and Kassie and Workie [28]. The studies stated that one of the factors that influence the occurrence of stunting in children is the mother's education and knowledge.…”
Section: Discussionsupporting
confidence: 86%
“…Children whose mothers/caregivers had not received IYCF counselling were eight times more likely to have acute malnutrition than were children whose mothers/caregivers had received IYCF counselling. These ndings coincide with those of Gambella town, Southwest Ethiopia (24). This could be attributed to the fact that counselling mothers/caregivers on infant and young child feeding increases awareness of optimal child feeding and caring practices.…”
Section: Discussionsupporting
confidence: 76%
“…Mothers with better knowledge of children's nutritional health and prevention of infectious diseases will have awareness in providing better health care for their children and better prevention treatment of infective diseases. It can be concluded that the better the mother knows about the health status of her child, the lower the stunting rate in her child [9]. Increased knowledge of infectious diseases in housewives can be obtained from various sources such as posyandu activities which are one of the means for mothers of toddlers to increase their knowledge.…”
Section: Knowledge Of Infectious Diseasesmentioning
confidence: 99%